Design and simulation of Clamped-Clamped and Clamped-Free resonators - Zainuddin, Ahmad Anwar; Karim, Jamilah; Nordin, Anis Nurashikin; Pandian, Mohanraj Saundara; Khan, Sheroz (Institute of Electrical and Electronics Engineers, Inc, 2013)
To date, there have been interests in designing the Micro-Electro-Mechanical System (MEMS) integrated with Complementary Metal-Oxide Semiconductor (CMOS) resonator for RF integrated circuits. This work presents the design of Clamped-Clamped (CC) and Clamped-Free (CF) beam resonators. These resonators provide on-chip low cost solutions for devices with much reduced chip area, besides having considerably reduced insertion losses due to nonexistent external bond wires. They can be integrated with amplifiers to form oscillators for generating clocks in the 2MHz and 20MHz range. The resonators require DC voltage maximally 10V for Clamped-Clamped and 7V for Clamped-free and 100mV AC voltage to electrostatically actuate the resonator's beams. The actuation is simulated and measured using Finite Element modeling software of COMSOL to obtain optimum design parameters. This paper makes a comparative review of different models for evaluating the designed resonator's performance in terms of resonance frequency under given pull-in voltage, and appropriate displacement.